Author Correction: Transneuronal propagation of mutant huntingtin contributes to non–cell autonomous pathology in neurons. (September 2018) - Pecho-Vrieseling, Eline; Rieker, Claus; Fuchs, Sascha; Bleckmann, Dorothee; Esposito, Maria; Botta, Paolo; Goldstein, Chris; Bernhard, Mario; Galimberti, Ivan; Müller, Matthias; Lüthi, Andreas; Arber, Silvia; et al.
In the version of this article initially published, the catalog numbers for BoNT A and B were given in the Methods section as T0195 and T5644; the correct numbers are B8776 and B6403. The error has been corrected in the HTML and PDF versions of the article.